Overexpression of the obesity hormone leptin in human colorectal cancer - Koda, Mariusz (BMJ Group, 2007)
BACKGROUND: Leptin is an adipocyte‐derived neurohormone, high levels of which are found in obese individuals. Leptin controls energy expenditure, acting in the brain, and regulates different processes in peripheral organs. Recent studies have suggested that leptin may be involved in cancer development and progression. AIMS: To analyse leptin expression in human colorectal cancer as well as in colorectal mucosa and colorectal adenomas. METHODS: Leptin expression was assessed by immunohistochemistry in 166 colorectal cancers, 101 samples of colorectal mucosa and 41 adenomas. Leptin concentration in colorectal cancer was correlated with selected clinicopathological features. RESULTS: Immunoreactivity for leptin was observed in 51.2% (85/166) of primary colorectal cancers. In adenomas leptin expression was observed in 14.6% (6/41) of studied cases. In normal mucosa, leptin was present at low levels, except in tumour bordering areas where its concentration appeared to reflect levels in the adjacent cancer tissue. Leptin expression in colorectal cancer significantly correlated with tumour G2 grade (p = 0.002) as well as with histological type (adenocarcinoma) of tumours (p = 0.044). CONCLUSIONS: Results indicate that leptin is overexpressed in human colorectal cancer, which suggests that the hormone might contribute to colorectal cancer development and progression.